2023
DOI: 10.1093/ckj/sfac225
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of 10 candidate genes causing Mendelian calcium nephrolithiasis in the INCIPE study: a South European general population cohort

Abstract: Background Idiopathic calcium nephrolithiasis (ICN) is a common condition with different a complex phenotype influenced by both environmental and genetic factors. In our study we investigated the association of allelic variants with the history of nephrolithiasis. Methods We genotyped and selected 10 candidate genes potentially related to risk of ICN from 3046 subjects participating in the INCIPE survey (Initiative on Nephrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In their seminal study, Schlingmann and co-workers found recessive mutations in CYP24A1, the gene encoding 25-hydroxyvitamin D 24-hydroxylase, the key enzyme involved in the degradation of 1,25-dihydroxy vitamin D3, in six children with spontaneous hypercalcemia and also in a cohort of neonates in whom severe hypercalcemia developed after vitamin D administration [ 98 ]. Since then, many studies have reported a strong association between an increased risk of forming urinary stones and some genetic variants in the CYP24A1 gene, VDR gene polymorphisms, or other genetic variants of some specific solute transporters (SLC34A1, SLC34A3), suggesting that some individuals may be more prone than others to suffer from pro-lithogenic effects of vitamin D administration [ 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Risks For Vitamin D And/or Calcium Supplementation In Ul Pat...mentioning
confidence: 99%
“…In their seminal study, Schlingmann and co-workers found recessive mutations in CYP24A1, the gene encoding 25-hydroxyvitamin D 24-hydroxylase, the key enzyme involved in the degradation of 1,25-dihydroxy vitamin D3, in six children with spontaneous hypercalcemia and also in a cohort of neonates in whom severe hypercalcemia developed after vitamin D administration [ 98 ]. Since then, many studies have reported a strong association between an increased risk of forming urinary stones and some genetic variants in the CYP24A1 gene, VDR gene polymorphisms, or other genetic variants of some specific solute transporters (SLC34A1, SLC34A3), suggesting that some individuals may be more prone than others to suffer from pro-lithogenic effects of vitamin D administration [ 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Risks For Vitamin D And/or Calcium Supplementation In Ul Pat...mentioning
confidence: 99%
“…Prior studies have suggested that certain clinical and radiologic features of kidney stones are associated with disease recurrence [ 7–9 ]. In addition to traditional risk factors, genetics also play a key role in nephrolithiasis [ 10 ]. Single nucleotide polymorphism (SNP) is one of the most common types of genetic differences among humans.…”
Section: Introductionmentioning
confidence: 99%